The tonadilla in performance : lyric comedy in enlightenment Spain - Le Guin, Elisabeth, 1957- (University of California Press, 2013)
The tonadilla, a type of satiric musical skit popular on the public stages of Madrid during the late Enlightenment, has played a significant role in the history of music in Spain. This book, the first major study of the tonadilla in English, examines the musical, theatrical, and social worlds that the tonadilla brought together and traces the lasting influence this genre has had on the historiography of Spanish music. The tonadillas' careful constructions of musical populism provide a window onto the tensions among Enlightenment modernity, folkloric nationalism, and the politics of representat.